Coconut husk remover - Mohd Haziq, Nordin (2009)
Coconut Husk Remover is a tool to remove coconut husk. There are many type of coconut husk remover in the market such as pointy machete, pointy stick and basic coconut opener. Unfortunately, the method is dangerous and hard to operate. A new coconut husk remover will be development in this study to overcome the problem. Design and fabricates of a new coconut husk remover including several process. There are many process involve to fabricate the product such as gathering material, measuring, cutting material, drilling, joining, grinding, and product finishing process. A new coconut husk remover will be fabricating. It can open the coconut husk easily and safely.